2019
DOI: 10.1177/0197918319893292
|View full text |Cite
|
Sign up to set email alerts
|

Some Media Matter More Than Others: Investigating Media Effects on Attitudes toward and Perceptions of Immigration in Sweden

Abstract: Over the last decade, issues related to immigration have become increasingly salient across Western democracies. This increasing salience has made it more important to understand people’s attitudes toward immigration, including the effects of media use on those attitudes. Differentiating between attitudes toward different types of immigration, attitudes toward immigration from different parts of the world, and perceptions of immigration’s impact, this article investigates the effects of media use on attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Another answer might be that although numerous studies have shown that media can have effects on public attitudes, this is not always the case (Shehata & Falasca, 2014; Theorin & Strömbäck, 2020). People are equipped with several sources of resistance to media influence (Blinder & Jeannet, 2017; Pomerantz et al, 1995; Slothuus & de Vreese, 2010; Taber & Lodge, 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Another answer might be that although numerous studies have shown that media can have effects on public attitudes, this is not always the case (Shehata & Falasca, 2014; Theorin & Strömbäck, 2020). People are equipped with several sources of resistance to media influence (Blinder & Jeannet, 2017; Pomerantz et al, 1995; Slothuus & de Vreese, 2010; Taber & Lodge, 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Alternative media have become increasingly important as a source of news, especially so for populist voters who show significantly lower levels of trust in mainstream media and largely seek their news via non-traditional channels (Hagelund 2020). There is also evidence to suggest that alternative media is more powerful than traditional media in shaping immigration attitudes of the reader/viewer in both leftist and rightist fora (Theorin and Strömbäck 2020). This is of course partly a result of such media's tendency to encapsulate the users into ever narrower echo-chambers without dissenting views.…”
Section: The Mediamentioning
confidence: 99%
“…Many of the above-mentioned studies only analyse single medium at most to compare countries. Other studies, instead, are located in single country (Czymara and Dochow, 2018;Nora and Strömbäck, 2020), strongly featured i.e., for the development of the digital platform, the relationship between public and commercial broadcasting, or the national journalistic culture.…”
Section: Media Effects On Social Systemsmentioning
confidence: 99%